Hyaluronan negatively regulates vascular calcification involving BMP2 signaling. (October 2018) - Kong, Yonglun; Liang, Qingchun; Chen, Yanting; Yang, Pingzhen; Liu, Xiaoyu; Li, Yining; Feng, Siyuan; Wu, Ji; Liu, Wantao; Tang, Jingyi; Yu, Huimin; Ou, Jing-Song; et al.
Abstract Vascular calcification is a highly regulated biological process similar to bone formation involving osteogenic differentiation of vascular smooth muscle cells (VSMCs). Hyaluronan (HA), a major structural component of the extracellular matrix in cartilage, has been shown to inhibit osteoblast differentiation. However, whether HA affects osteogenic differentiation and calcification of VSMCs remains unclear. In the present study, we used in vitro and ex vivo models of vascular calcification to investigate the role of HA in vascular calcification. Both high and low molecular weight HA treatment significantly reduced calcification of rat VSMCs in a dose-dependent manner, as detected by alizarin red staining and calcium content assay. Ex vivo study further confirmed the inhibitory effect of HA on vascular calcification. Similarly, HA treatment decreased ALP activity and expression of bone-related molecules including Runx2, BMP2 and Msx2. By contrast, inhibition of HA synthesis by 4-methylumbelliferone (4MU) promoted calcification of rat VSMCs. In addition, adenovirus-mediated overexpression of HA synthase 2 (HAS2), a major HA synthase in VSMCs, also inhibited calcification of VSMCs, whereas CRISPR/Cas9-mediated HAS2 knockout promoted calcification of rat A10 cells. Furthermore, we found that BMP2 signaling was inhibited in VSMCs after HA treatment. Recombinant BMP2 enhanced high calcium and phosphate-induced VSMC calcification, which can be blocked by HA treatment. Taken together, these findings suggest that HA inhibits vascular calcification involving BMP2 signaling. Hyaluronan (HA) is known to inhibit osteoblast differentiation, but its importance in vascular calcification needed clarification. In this study, the authors identify HA as a novel negative regulator of osteogenic differentiation of vascular smooth muscle cells via bone morphogenetic protein 2 signaling. These results indicate that HA may be a novel potential therapeutic agent for the treatment of vascular calcification.